A hybrid haptic stimulation wearable device to recover the missing sensation of the upper extremity prostheses’ users - Abdullah, Abdullah I.; Mat Isa, Norasikin; Nemah, Mohammed Najeh; Fakhri, O M; Kareem, A. K. (TRKU, 2020)
A hybrid haptic feedback stimulation system that is capable in sensing the surface texture, and the temperature, simultaneously, was designed for a prosthetic hand to provide a tactile sensation to amputation patients. In addition, the haptic system was developed to enable the prosthetic’s users to implement withdrawal reflexes due to the thermal noxious stimulus in a quick manner. The re-sensation is achieved by non-invasively stimulating the skin of the patients’ residual limbs, based on the type and the level of tactile signals provided by the sensory system of the prostheses. Accordingly, a novel hybrid pressure-vibration- temperature feedback stimulation system was design to provide a huge information regarding the prostheses environment to the users without brain confusing or requiring long pre-training. An evaluation of sensation and response will be performed with healthy volunteers to evaluate the ability of the haptic system to stimulate the human nervous system. The results were presented in term of Stimulus Identification Rate (SIR). The test results and the volunteers' response established evidence that amputees are able to recover their sense of the contact pressure, the surface texture, and the object temperature as well as to perform thermal withdrawal reflexes using the solution developed in this work.